El rol de la mujer indígena en los procesos de elección popular del cantón Saraguro - Macas Chalán, Rosa Clementina (2022)
Different cultures have the right to coexist and the fundamental task of the state is to preserve them. Owning to the great protests of women for their rights to equality, justice and democracy; however, women have still been marginalized. In this context, the present study aims to examine the role of indigenous women in the popular election processes of the Saraguro canton. For this purpose, the information for the present study has been taken from the database of the electoral Ecuadorian council (CNE) considering the sectional elections of the Saraguro canton during 2009, 2014 and 2019 election periods. In addition, focus groups were conducted by female leaders from two political organizations in Saraguro canton, from which it can be determined that women’s participation is minimal in the popular election processes. It is clear that gender inequality still prevails, even when women take part of political roles. In this context, a strategy is presented to increase the participation of women in the processes of sectional popular elections in the Saraguro canton.